Pengaruh Penggunaan Komik Digital terhadap Hasil Belajar Aqidah Akhlak - Fauziyah, Litsa Nailul (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This study aims to determine whether or not there is an effect of using digital comics on the learning outcomes of aqidah akhlak. This study uses a quantitative approach with a type of quasi experimental design. The population in this study were all students of MI Al-Hikmah Songgon Banyuwangi in the 2022/2023 academic year and the sampling technique in this study used purposive sampling with a total sample size of 36 respondents taken from class IA and IB students of MI Al-Hikmah Songgon Banyuwangi in the 2022/2023 academic year. Data collection techniques using pretest and posttest results. The data analysis technique used is the Independent Sample t test which utilizes SPSS 25 for windows. Based on the results of data analysis that has been processed with the Independent Sample T test, the sig. result is 0.000 < α 0.05 with a tcount of 9.833, and ttable 1.688 (N = 36), because tcount> ttable then Ha is accepted and H0 is rejected, which means that there is a significant effect on the use of digital comics on the learning outcomes of aqidah akhlak. So it can be concluded that the use of digital comics affects the learning outcomes of aqidah akhlak.